STUDI KASUS PENYIDIKAN TERHADAP TINDAK PIDANA PEMALSUAN SURAT KEPUTUSAN PENGANGKATAN GURU HONORER NOMOR : 800/35/2005 UNTUK PERSYARATAN PROGRAM SELEKSI CALON PEGAWAI NEGERI SIPIL (CPNS) KABUPATEN WONOGIRI TAHUN 2014 - MUSTA’IN, MUSTA’IN (Dinamika Hukum, 2016)
Investigation Crime of Forgery Decree Honorary Teacher Appointment No. 800/35/2005, the Program Selection Requirements Candidates for Civil Servants (CPNS) Wonogiri 2014, is one form of investigations conducted by police investigators. This investigation was intended to verify a report or reports or information regarding the Crime of Forgery Mail. Police as an institution in charge of the investigation and the investigation into a criminal offense are still many obstacles and constraints in the execution of his duties. The purpose of this study was to determine and analyze the law enforcement process against the perpetrators of the Crime of Forgery Decree of Appointment of Teachers Honorary Number: 800/35/2005, the To Requirements Program Selection of Civil Servants (CPNS) Wonogiri 2014, in accordance with the Criminal Code and Criminal Procedure Code in Wonogiri district police jurisdiction as well as identify and analyze the obstacles that arise in the implementation of the law enforcement process and how to overcome them. Methods of criminal law enforcement against crime Crime of Forgery Decree of Appointment of Teachers Honorary Number: 800/35/2005, the To Requirements Program Selection of Civil Servants (CPNS) Wonogiri 2014, based on these codes are included in this type of research juridical sociological is a descriptive study. Types and sources of data used are primary and secondary data. Data collection techniques with interviews and literature, while the analysis using qualitative analysis. It can be concluded that the law enforcement process against the perpetrators of the Crime of Forgery Decree of Appointment of Teachers Honorary Number: 800/35/2005, the To Requirements Program Selection of Civil Servants (CPNS) Wonogiri 2014, is in conformity with the Codes in the Region Police law Wonogiri this is reflected in Article 7 of the Criminal Procedure Code action in the form of arrest, detention, searches and seizure and calling people to be heard and a check as a suspect or a witness. Key Words : Investigation analysis, the crime of counterfeiting